(untitled) (International Journal of Environmental Sciences, 2024)
This study examined the COVID-19 pandemic’s various effects on students, emphasizing the social, emotional, economical, and intellectual difficulties they faced while under quarantine. Fifteen students from the Integrated Laboratory School in Grades 7 through 10 had their lived experiences recorded using a qualitative phenomenological study design. Purposive sampling was used to choose participants, who ranged in age from 13 to 17. Semi-structured online interviews using Zoom and Google Meet were used to collect the data, which were then subjected to theme phenomenological analysis. Four main themes emerged from the findings. First, students encountered academic difficulties that were characterized by interrupted instruction, inadequate internet connectivity, restricted access to technology, limited teacher-student engagement, and waning desire. Secondly, students and their families were severely affected by financial hardships; many households faced food insecurity, income loss, and the inability to pay for educational materials. Third, emotional and psychological issues surfaced, such as anxiety, fear, stress, loneliness, insomnia, and future uncertainty. Finally, social isolation affected family dynamics and peer interactions, which worsened emotional suffering and feelings of loneliness. The study came to the conclusion that the pandemic increased already existing gaps among students by acting as a health crisis as well as an educational, economic, and even environmental disaster. The findings highlight the need for equitable access to technology, strengthened mental health support systems, and inclusive educational interventions to enhance resilience during future crises.